2015
DOI: 10.1016/j.egypro.2015.03.236
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plate Spacing in Plate Heat Exchanger Design as a Condenser in Organic Rankine cycle for Low Temperature Heat Source

Abstract: Plate spacing is one of variable that influences plate heat exchanger (PHE) design as a condenser in Organic Rankine Cycle (ORC) system. The rises of plate spacing have effects to channel cross sectional area, channel velocity, equivalent diameter, and Reynold number at hot and cold fluid sides in PHE. Those parameters affect the total heat transfer area and total pressure drop that influence the PHE condenser performance. This paper investigated the detail effect of the plate spacing increments in the final t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…Dimana 𝑄 π‘π‘œπ‘™π‘‘ adalah heat flow rate fluida dingin (W), 𝑄 β„Žπ‘œπ‘‘ adalah heat flow rate fluida panas (W), π‘š π‘π‘œπ‘™π‘‘ adalah laju massa aliran fluida dingin (kg/jam), π‘š β„Žπ‘œπ‘‘ adalah laju massa aliran fluida panas (kg/jam), 𝐢𝑝 π‘π‘œπ‘™π‘‘ adalah kapasitas panas massa fluida pendingin (J/kg.K), 𝐢𝑝 β„Žπ‘œπ‘‘ adalah kapasitas panas massa fluida panas (J/kg.K), 𝑑 1 adalah suhu aliran fluida dingin masuk (K), 𝑑 2 adalah suhu aliran fluida dingin keluar (K), 𝑇 1 adalah suhu aliran fluida panas masuk (K), 𝑇 2 adalah suhu aliran fluida panas keluar (K) [8].…”
Section: Tabel 2 Karakteristik Pelatunclassified
See 1 more Smart Citation
“…Dimana 𝑄 π‘π‘œπ‘™π‘‘ adalah heat flow rate fluida dingin (W), 𝑄 β„Žπ‘œπ‘‘ adalah heat flow rate fluida panas (W), π‘š π‘π‘œπ‘™π‘‘ adalah laju massa aliran fluida dingin (kg/jam), π‘š β„Žπ‘œπ‘‘ adalah laju massa aliran fluida panas (kg/jam), 𝐢𝑝 π‘π‘œπ‘™π‘‘ adalah kapasitas panas massa fluida pendingin (J/kg.K), 𝐢𝑝 β„Žπ‘œπ‘‘ adalah kapasitas panas massa fluida panas (J/kg.K), 𝑑 1 adalah suhu aliran fluida dingin masuk (K), 𝑑 2 adalah suhu aliran fluida dingin keluar (K), 𝑇 1 adalah suhu aliran fluida panas masuk (K), 𝑇 2 adalah suhu aliran fluida panas keluar (K) [8].…”
Section: Tabel 2 Karakteristik Pelatunclassified
“…Selisih overall heat coefficient perhitungan dan trial dapat digunakan jika < 5% [8]. Jika tidak memenuhi, perlu dilakukan trial ulang nilai π‘ˆ hingga mendapatkan nilai yang sesuai.…”
Section: Effective Plate Heat Transfer Area (A)unclassified
“…The two-phase design method stems from the methodology outlined by Rohmah et al [38]. The governing equations are the same as for the single phase, with Reynolds number expressions Equations ( 9) and ( 10):…”
Section: Plate Heat Exchangermentioning
confidence: 99%
“…In literature a number of studies can be found on simultaneous optimization of plate heat exchangers used as evaporators and/or condensers and thermodynamic cycle design, mostly focusing on low temperature applications and pure fluids. Some of the works are related to the assessment of the impact of some specific cycle parameters on the PHE design [19,20], whilst other studies performed combined cycle-PHE optimization procedures with the aim of maximizing the cycle efficiency [21], and by including also an economic analysis [22,23]. The pressure drops were mostly considered as pumping cost on the heat source/sink side, and none of the studies assessed the impact of the working fluid pressure drops on the outlet condition of the evaporator.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%